Association between hepatitis B virus infection and chronic kidney disease: A cross-sectional study from 3 million population aged 20 to 49 years in rural China - Du, Ye; Zhang, Shikun; Hu, Mei; Wang, Qiaomei; Liu, Na; Shen, Haiping; Zhang, Yiping; Yan, Donghai; Zhang, Man (Medicine (Baltimore), 2019)
Hepatitis B virus (HBV) infection can lead to different types of chronic kidney diseases (CKD) in clinical practice. However, HBV infection has been observed to have no significant association with CKD indicators in some epidemiological surveys. This research aims to estimate CKD prevalence in HBV infection population and clarify the relationship between HBV infection status and CKD.The participants aged 20 to 49 years were selected by multistage random sampling from January 1, 2010 to December 31, 2012 across 31 provinces and regions in rural China. The data was collected by standard questionnaire and physical check-up. Status of HBV infection was diagnosed as immune tolerant phase, hepatitis B envelope antigen -positive chronic HBV infection, inactive HBV carrier, hepatitis B envelope antigen -negative chronic HBV infection and resolved HBV infection based on serological markers, and the level of hepatic function, respectively.In total, 2,969,502 subjects were included in the study. In population aged 20 to 49 years in rural China, prevalence of HBV infection was 12.17%. Prevalence of proteinuria, hematuria, estimated glomerular filtration rate less than 60 mL/min/1.73m and CKD was 0.94%(95% CI = 0.91-0.97%) vs. 0.65%(95% CI = 0.64-0.66%), 1.92%(95% CI = 1.87-1.96%) vs. 1.19% (95% CI = 1.18-1.21%), 1.02%(95% CI = 0.99-1.06%) vs. 0.77% (95% CI = 0.76-0.78%), and 3.85%(95% CI = 3.78-3.91%) vs. 2.60%(95% CI = 2.58-2.62%) in population with HBV infection and without infection, respectively. Prevalence of CKD and indicators was higher in population in every status of HBV infection than in population without infection, respectively (all P < 0·0001). Every HBV infection status was a risk factor for CKD.CKD prevalence was higher in population in every status of HBV infection than without infection. HBV infection was a risk factor for CKD in population aged 20 to 49 years in rural China.